2013
DOI: 10.1080/01140671.2013.772905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated carbon dioxide and soil nitrogen on growth of two leafyBrassicavegetables

Abstract: Elevated atmospheric carbon dioxide (CO 2 ) increases the instantaneous rate of photosynthesis in C 3 plants. With ample nutrients and water, this so-called 'CO 2 fertilization effect' generally leads to improved growth and production of many plant species that humans use as food. To determine whether increasing CO 2 could be beneficial to growth and yield of leafy Brassica vegetables, trials were established in a Free Air CO 2 Enrichment facility at Horsham, Australia using projected atmospheric CO 2 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…AGFACE facilities were outdoor laboratories (see Fig. 1 for an example) where the impacts of expected e[CO 2 ] in the year 2050 (550 µmol/mol) on crops were examined [1 , 7 , 8 , 9 , 10 , 11] . The AGFACE facilities were built to understand the impacts of different combinations of irrigation, nitrogen fertilizer and time of sowing (TOS) treatments at two locations and across different soil types under e[CO 2 ] on a range of crops [9] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AGFACE facilities were outdoor laboratories (see Fig. 1 for an example) where the impacts of expected e[CO 2 ] in the year 2050 (550 µmol/mol) on crops were examined [1 , 7 , 8 , 9 , 10 , 11] . The AGFACE facilities were built to understand the impacts of different combinations of irrigation, nitrogen fertilizer and time of sowing (TOS) treatments at two locations and across different soil types under e[CO 2 ] on a range of crops [9] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Eight plots under e[CO 2 ] treatment (4-m diameter rings) were established along with eight a[CO 2 ] control plots. The experiment measured the interacting effects of e[CO 2 ], nitrogen (low/high) and two Brassica rapa cultivars on shoot growth under south-eastern Australian conditions [11] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The data regarding the influence of elevated carbon dioxide on Brassicaceae plants’ characteristics are scarce. An early study showed that two Brassica rapa cultivars grows at 550 ppmv CO 2 showed increased crop productivity, even with the high-end soil nitrogen [ 34 ]. An increase in chlorophyll content of 33% has been found for pak choi ( Brassica rapa ssp.…”
Section: Introductionmentioning
confidence: 99%
“…), crops and measurements (e.g. Thomson et al, 2013;Zhang et al, 2013;Manderscheid et al, 2014;Fernando et al, 2015). Empirical evidence of major plant responses exists, including stomatal closure and higher light-saturated photosynthesis rates (Ainsworth & Rogers, 2007;Leakey et al, 2009).…”
Section: Introductionmentioning
confidence: 99%